URGENSI IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMULIHAN PEMBELAJARAN - Ibnu, Ibnu; Irtati, Irtati; Maryani, Baiq; Anwar, Khairil; Sulfana, Evi Yanti (Jurnal Ilmiah Telaah, 2024)
Currently, the word "freedom to learn" is not foreign to Indonesian society, especially in the world of education. The independent learning curriculum was designed as an effort by the Ministry of Education and Culture to overcome the learning crisis that has long been faced due to the pandemic. The pandemic has influenced a learning crisis which is characterized by low student learning outcomes. The aim of the independent curriculum is so that education in Indonesia can be like developed countries where students have the freedom to choose according to their interests. Given this, the aim of writing this article is to provide information regarding the independent learning curriculum which is being implemented as an effort to restore learning in Indonesia today. This research is descriptive research with data collection techniques through online data searching or internet searching. In conclusion, the independent curriculum is an important component in the world of education, because the curriculum is a reference for organizing so that educational goals can be achieved. In this independent curriculum, it is prepared by the Government as the policy maker. However, it is the education units and teachers who are tasked with operationalizing and implementing the curriculum that has been prepared by the central government. Apart from that, seeing that there are several weaknesses in the independent curriculum, it is necessary to carry out socialization and adjustments first before the independent curriculum becomes the national curriculum.